In Vivo Confocal Microscopy and Biomicroscopy of Filtering Blebs After Trabeculectomy. Issue 4 (April 2016) - Caglar, Cagatay; Karpuzoglu, Nafiz; Batur, Muhammed; Yasar, Tekin
Abstract : Purpose: The aim of this study is to analyze filtering blebs (FBs) after trabeculectomy with in vivo confocal microscopy (IVCM) and slit-lamp biomicroscopy. Materials and Methods: IVCM using the Heidelberg Retina Tomograph/Rostock Cornea Module and biomicroscopic examination were performed in 67 FBs in 55 patients 3 months to 30 years postoperatively (mean, 3.2±2.1 y). Although the blebs were evaluated by slit-lamp biomicroscopy, standardized FB classification was used. Results: Of the patients, 9 were female (16.3%) and 46 were male (83.7%), ranging in age from 32 to 81 (51.5±13.2) years. The absence of vascularization and tortuous vessels and the presence of epithelial microcysts on the bleb were significantly correlated with good bleb function ( P =0.001). IVCM findings significantly correlated with good bleb function, including the number of epithelial microcysts ( P =0.002), the stromal cysts without capsule ( P <0.001), minimal vascularization ( P =0.002), and the absence of tortuous conjunctival vessels ( P =0.003) and reticular and trabecular bleb patterns ( P =0.01 and <0.01, respectively). In contrast, a hyperreflective condensed bleb stroma was significantly associated with bleb failure ( P <0.001). Conclusions: IVCM supports biomicroscopic evaluation as the mainstay for FB analysis and permits diagnostic imaging of FBs to evaluate and follow-up the bleb, differentiation between good and insufficient bleb function, and a microscopic analysis at a cellular level including the structural pattern of the bleb.